Nutritional value and use of ligno-cellulosic feed treated with urea in the ruminant diet - Cañeque V.; Velasco S.; Sancha J.L. (Exploitation of Mediterranean roughage and by-products, 1998)
Urea is an interesting alternative to anhydrous ammonia in the treatment of ligno-cellulosic foodstuffs due to its lower cost and easier handling. The urea treatment is based on adequate ureolysis and on the effect of ammonia on the composition of the straw. Its outcome is influenced by a series of factors considered in the present study which include: dose of urea applied, initial quality and moisture content of the material treated, duration of the treatment and temperature conditions under which the treatment is applied.